1995
DOI: 10.1038/ki.1995.282
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate neutralizes peritoneal dialysate cytotoxicity: Maintained integrity and proliferation of cultured human mesothelial cells

Abstract: Toxic effects of commercially available peritoneal dialysate (PD) fluid include damage to mesothelial cells (MC), causing a severely disturbed proliferation of cultured MC. We investigated the injury to the cell membrane (by release of lactate dehydrogenase, LDH), the proliferation (by cell counts and by 3H-thymidine incorporation), and optional the cytokine generation (by IL-1 receptor-antagonist production, IL-1 ra) of cultured human MC during the 48 hours after a 30 minute exposure to PD containing either 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 21 publications
0
21
1
1
Order By: Relevance
“…So far, the evidence presented in this study, in addition to that previously reported by Brunkhorst and Mahiout [14, 15], is one more piece of information pointing at pyruvate as a possible protective buffer for peritoneal dialysis solutions. This approach finds further support from evidence indicating that pyruvate is freely diffusible from the intravascular to the intercellular, intracellular and mitochondrial compartments [40, 48, 49].…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…So far, the evidence presented in this study, in addition to that previously reported by Brunkhorst and Mahiout [14, 15], is one more piece of information pointing at pyruvate as a possible protective buffer for peritoneal dialysis solutions. This approach finds further support from evidence indicating that pyruvate is freely diffusible from the intravascular to the intercellular, intracellular and mitochondrial compartments [40, 48, 49].…”
Section: Discussionmentioning
confidence: 75%
“…Studies done in human mesothelial cells in culture [13]detected the presence of intracellular antioxidant capability. Other in vitro studies [14, 15, 16]showed that pyruvate anions can neutralize the cytotoxic effects of peritoneal dialysis fluids upon cultured mesothelial cells that showed, unlike observations made using lactated solutions, increased proliferation and IL-6 production. We speculated that this additional information could be, at least in part, explained on the basis of the scavenger effect of pyruvate upon oxidants.…”
Section: Introductionmentioning
confidence: 99%
“…As NAD + is an essential electron acceptor in glycolysis, its exhaustion may paralyze the glycolysis pathway [24, 25]. Furthermore, there is evidence that lactate can modulate cell function by accelerating the glucose-driven polyol pathway and intracellular sorbitol accumulation [26, 27]. Lactate – alone or in conjunction with glucose – augmented HPMC activation, which could be blocked by the aldose reductase inhibitor sorbinil, thus indicating the involvement of the polyol pathway [28].…”
Section: Discussionmentioning
confidence: 99%
“…Between the hypertonic glucose-based solutions, we found a significantly higher release of the cytokines constitutively released by PBMCs incubated in pyruvate-buffered solutions (p = 0.01), but no difference when the cells were stimulated with LPS. In an in vitro model of cultured human mesothelial cells, pyruvate neutralizes PD cytotoxicity and this effect is even more pronounced with the hypertonic glucose solution [37]. …”
Section: Discussionmentioning
confidence: 99%